An adaptive optimisation method for multimedia services in wireless networks. (13th March 2012) - Ling, Yutao; Yi, Benshun; Wu, Jianbin; Yao, Yuan
In next–generation wireless networks, effective management of the limited radio resources is very important to provide mobile multimedia services with Quality of Service (QoS) guarantees. Many mechanisms based on Bandwidth Reservation (BR) have been proposed to decrease connection blocking/dropping probability. In this paper, we propose an adaptive and dynamic reservation as well as Call Admission Control (CAC) method for multimedia traffic in wireless systems. The analytical results are supported by simulation and show that this work improves the service quality by minimising the new Call Blocking Probability (CBP) and handoff Call Dropping Probability (CDP).